Supporting and Protecting Residents Experiencing Homelessness in the Nation's Largest Cities During COVID-19 - Nichols, Gabrielle; Mays, Max (Journal of public health management and practice, 2021)
Large urban health departments developed and implemented various approaches to prevent COVID-19 outbreaks and promote the health and well-being of individuals experiencing homelessness and housing insecurity throughout the pandemic. Reviewing the approaches of several large urban health departments, the most frequent practices included increasing housing options, on-the-ground outreach and resource allocation, and integrated communications. Key steps necessary to develop and implement these policies and procedures are discussed, and innovative approaches are highlighted.